CAMPAIGN FOR MORALITY AND HEALTH IN GENERATION Z - Silvia Putri, Enda; marniati, marniati; Mulyani, Itza; Khairunnas, Khairunnas; Elida, Sukma (RADJA PUBLIKA, 2023)
The significance of living in today's world as a moral, healthy member of generation Z. The digital era, which is characterised by easy access to information and cutting-edge technology, is the environment in which Generation Z develops and evolves. The purpose of the initiative is to assist generation Z in overcoming difficulties brought on by low moral risk, a lack of health awareness, and a lack of work-related drive. The method used in a campaign to teach schoolgirl students in generation Z healthy and moral behaviour through lectures looks up. Results indicate which female students learn more about developing moral and healthy behaviours and about expanding comprehension to lessen the possibility of being subjected to associations and media that have unfavourable effects on their morals and health. The conclusion of concurrent campaigns can assist generation Z in defending themselves against the damaging influence of associations and media that affect their morals and physical well-being.